Understanding Positivism: A Qualitative Exploration of Its Principles and Relevance Today - Khanday, Sumbl Ahmad; Vali, Karanam Mahaboob; Junaid, Md.; Ahmad, Masood (European Journal of Applied Sciences, 2024)
This paper embarks on a journey to illuminate the philosophy of positivism, a perspective that has profoundly shaped our understanding of knowledge, truth, and reality. Positivism, with its unwavering focus on observable facts and empirical evidence, offers a framework for navigating the complexities of the modern world. Yet, despite its foundational influence on scientific inquiry and societal development, it remains a concept shrouded in confusion for many. Through a qualitative exploration, this paper seeks to bridge the gap between academic discourse and everyday understanding, unravelling the essence of positivism in a way that resonates with the general population. By tracing its historical roots, dissecting its core principles, and reflecting on its relevance in contemporary society, this work invites readers to reconsider how they perceive and interact with the world around them. In a time when the line between fact and belief is increasingly blurred, this paper argues for the enduring importance of positivism as a guiding philosophy. It challenges readers to engage with positivist though not as an abstract academic exercise, but as a practical approach to making sense of their lived experiences and the broader social landscape.